2002
DOI: 10.1136/jme.28.5.303
|View full text |Cite
|
Sign up to set email alerts
|

Increasing use of DNR orders in the elderly worldwide: whose choice is it?

Abstract: Most elderly patients die with an order in place that they not be given cardiopulmonary resuscitation (DNR order). Surveys have shown that many elderly in different parts of the world want to be resuscitated, but may lack knowledge about the specifics of cardiopulmonary resuscitation (CPR). Data from countries other than the US is limited, but differences in physician and patient opinions by nationality regarding CPR do exist. Physicians' own preferences for CPR may predominate in the DNR decision making proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 113 publications
0
49
1
Order By: Relevance
“…Several studies suggested that patients would decline quantity of life in the absence of quality [1]. A common misunderstanding patients and families have is that CPR would keep patients alive and living as they were before the code.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies suggested that patients would decline quantity of life in the absence of quality [1]. A common misunderstanding patients and families have is that CPR would keep patients alive and living as they were before the code.…”
Section: Discussionmentioning
confidence: 99%
“…European studies had revealed that physicians' and patients' religion could cause significant differences in the use of end-of-life therapies with values and practices differing from country to country [13]. Differences in training and personal religious beliefs have been suggested as responsible for variations in attitudes [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 This is problematic because family members are frequently unfamiliar with the procedures involved in CPR, lack accurate information about patients' prognoses, and routinely overestimate patients' preferences for CPR and other life-sustaining treatments. 31,32 DNR discussions fail to satisfy criteria for informed consent. DNR discussions often omit essential information to allow patients or surrogates to make informed decisions.…”
Section: Problems With Dnr Orders In Practicementioning
confidence: 99%
“…However, even if a patient has a poor prognosis, it does not always mean that he/she does not wish to be resuscitated or receive aggressive treatment. As the final decision on DNAR orders will differ according to the attitude of the individual patient,10, 11, 12, 13 it is essential to confirm each and every patient's intentions wherever possible. Apart from these diseases and background factors, patients with sequelae of cerebrovascular disease or dementia or patients in a persistent vegetative state may lack decision‐making capability.…”
Section: Discussionmentioning
confidence: 99%